Analysis of Human Resources and IT Infrastructure Readiness in the Implementation of the Electronic Medical Record System at the UPT Puskesmas Rawat Inap Lolofitu Moi - Marbun, William Jhonson; Mendrofa, Syah Abadi; Halawa, Odaligoziduhu; Telaumbanua, Eliagus (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the readiness of human resources (HR) and information technology (IT) infrastructure in supporting the implementation of the Electronic Medical Record System (EMR) at the UPT Puskesmas Rawat Inap Lolofitu Moi. The background of this research is grounded in the importance of digital transformation in the healthcare sector and the obligation for health facilities to adopt EMR systems as stipulated in national regulations. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation with key informants, including the head of the health center, medical record officers, and the head of administration. The findings reveal that HR readiness is in the "moderately ready" category, characterized by motivation, positive attitudes, basic understanding, and confidence among staff in using the EMR. However, managerial support remains limited, as indicated by the lack of technical training, mentoring, and optimal digital system operational skills. The condition and availability of IT infrastructure are found to be highly inadequate, with only one laptop and printer (without a scanner), a damaged main computer, unstable internet connectivity, inactive software, and the absence of a data backup system. Furthermore, there are no technical SOPs or dedicated IT staff, exacerbating implementation challenges. The current manual, paper-based recording process results in slow services and higher risks of data errors. The success of EMR implementation depends on addressing urgent needs, such as regular training, hardware procurement, network upgrades, IT staff placement, SOP development, and coordination with the health office. These findings provide a concrete picture of the internal readiness challenges faced by health centers in the digital transformation of healthcare services.